The Use Of A Graphic Mini-Computer System As A Rock Mechanics And Roof Support Design Tool - Robert M. Cox (International Conference on Ground Control in Mining, 1982)
The successful application of the science of rock mechanics to the practical problems of coal mine design requires the acquisition and reduction to useable form of large amounts of field and laboratory data, and the construction and analyses of numerous geostructural models containing a wide variety of geometric and physical strength variables. Typically, the rime constraints placed on a new mine design project coupled with the inherent complexities of a good rock mechanics study combine to limit the applications of rock mechanics to the most rudimentary level. To facilitate a better application of rock mechanics to mine design problems, an interactive software package has been developed for use on a graphic mini-computer system that serves to aid the engineer in the timely and efficient analyses of rock mechanics data and geostructural models. The first phase of the rock mechanics package solicits the input of the raw geologic and rock strength data, analyzes and arranges this data in a logical manner, produces complete listings and statisitical summaries of the various rock properties, and stores the data on magnetic tapes and disks to serve as a future Rock Mechanics Data Base. The second phase of the software package provides for the analyses of a variety of geostructural models using a wide variety of geometric variables coupled with the rock strength data stored in the Rock Mechanics Data Base. This software package allows for the evaluation of numerous geostructural mine models for the design and selection of mine roof support and pillar systems (see Table l).